2022
DOI: 10.1177/00033197221094409
|View full text |Cite
|
Sign up to set email alerts
|

Association of Controlling Nutritional Status Score With Adverse Outcomes in Patients With Coronary Artery Disease: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis sought to examine the association between the controlling nutritional status (CONUT) score and adverse outcomes in patients with coronary artery disease (CAD). PubMed and Embase databases were searched for eligible studies from their inceptions to December 12, 2021 to identify studies investigating the association of the CONUT score with major adverse cardiovascular events (MACEs) and all-cause mortality in CAD patients. Twelve studies (36,198 CAD) patients satisfied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…It was shown that nutritional status is correlated with the length of hospitalization in patients with hypertension and atrial fibrillation [ 26 , 27 ]. It is also associated with mortality in heart failure and coronary artery disease [ 28 , 29 , 30 , 31 , 32 ]. The available studies are mostly retrospective, so they are based only on the parameters available in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that nutritional status is correlated with the length of hospitalization in patients with hypertension and atrial fibrillation [ 26 , 27 ]. It is also associated with mortality in heart failure and coronary artery disease [ 28 , 29 , 30 , 31 , 32 ]. The available studies are mostly retrospective, so they are based only on the parameters available in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2 Coronary artery diseases have become a global health concern and a major cause of death in developed and developing countries. 2,3 In addition to high mortality, they have social, psychological, and physical consequences. 3 Coronary artery diseases are the leading causes of death in Iran accounting for approximately 40% of deaths.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In addition to high mortality, they have social, psychological, and physical consequences. 3 Coronary artery diseases are the leading causes of death in Iran accounting for approximately 40% of deaths. 4 Myocardial infarction (MI) is a common cause of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies, Czapla et al reported that nutritional status is correlated with the length of hospitalization in patients with hypertension and atrial fibrillation [ 13 , 14 ]. Moreover, nutritional status was also associated with mortality in patients with acute heart failure and coronary artery disease [ 15 , 16 , 17 , 18 , 19 ]. Furthermore, nutritional status is also associated with a better prognosis in chronic heart failure [ 20 ] and symptom severity in coronary heart disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%